KONSEPSI ALQURAN TENTANG MANUSIA - Irfan, Santoso (Institut Agama Islam Negeri (IAIN) Palu, 2007)
This article deals with the conception of the Qurâan on human beings. One of the major themes of the Qurâan is concernedÂ with human beings and their functions on the earth. The Qurâan speaks ofÂ human beingsÂ in various terms such as al-insan, al-basyar, -âabd and khalifah. The term Al-insan refers to the quality of thought and consciousness of human beingsâ; al-basyar signs their natural dimensions such as eating, drinking and dying; âabd Â indicates their obedience andÂ piety, and khalifah denotesÂ their freedom and creativity.Kata Kunci : Alquran, manusia, al-insan, al-basyar, âabd, Â Â khalifahÂ